DNA Damage Caused by Heme and Hemoglobin in Saccharomyces cerevisiae - Nyblom, My (My University, 2018)
Large quantities of blood that can be used in the medical world are needed, but the use of donated human blood comes with multiple limitations which makes the de-mand from the medical world hard to meet. Therefore, human heme and hemoglobin have been produced in metabolically engineered strains of Saccharomyces cerevisiae (S. cerevisiae) with the intention of using human hemoglobin as an oxygen carrier in synthetic blood. Heme and hemoglobin have been observed to reduce oxygen, leading to increased amounts of reactive oxygen species (ROS) that in turn can induce multiple types of cellular damage, including DNA damage. Hemoglobin has also been observed to induce DNA damage without the presence of ROS, so the mechanisms by which heme and hemoglobin can induce DNA damage is not fully understood. To further investigate and understand how DNA damage is induced by heme and hemoglobin is of interest both when it comes to a direct improvement of hemoglobin producing strains of S. cerevisiae and how heme and hemoglobin in future blood substitutions should be used in order to avoid cellular damage. In this study, a method for visualizing genomic DNA damage was adapted for heme and hemoglobin related DNA damage in S. cerevisiae. The genomic DNA damage, apoptotic features and oxidative levels were compared for two strains of S. cere-visiae, where one was engineered for overproduction of heme and hemoglobin. The strain overproducing heme and hemoglobin had increased oxidative levels, increased apoptosis, decreased growth and increased genomic DNA damage. The genomic DNA damage, correlated to growth, was compared for six di˙erent strains of S. cerevisiae. Overproduction of heme and hemoglobin was showed to in-duce increased levels of genomic DNA damage but without correlation to decreased growth, hemoglobin expression level or to be dependent on time. Furthermore, the results suggest that introduction of α-hemoglobin stabilizing protein and methe-moglobin reductase, both related to the stability and degradation of hemoglobin and involved in generation of ROS, decrease the genomic DNA damage.
Keywords: Mikrobiologi; Mikrobiologi inom det medicinska området; Medicinsk bioteknologi (med inriktning mot cellbiologi); Livsvetenskaper; Microbiology; Microbiology in the medical area; Medical Biotechnology (with a focus on Cell Biology); Life Science